Anatomical considerations of the inferior alveolar canal - Ruge-Jiménez, Omar Yamid; Camargo-Cañón, Oscar Andrés; Ortiz, Yudy Patricia (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Introduction: the knowledge of anatomical variations of the inferior alveolar canal is necessary for surgical procedures involving the mandible. The purpose was to determine the relationships and anatomical variations of the mandibular canal. Methods: a descriptive study was performed using 50 dry mandibles measuring distances of the mandibular foramen with respect to the anterior posterior and lower borders and the sigmoid notch, distances from the mental foramen to the basal border and the alveolar crest. Cuts were done in ramus and body to determine the relationship with close anatomical structures. Results: The mandibular foramen was found in 88% of the cases in the middle third of ramus. The distance from the foramen to the sigmoid notch was 19.78 ± 3.3 mm, to the anterior border was 17.46 ± 3.04 mm, to the posterior border was 12.2 ± 1.9 mm and to the inferior border was 26.4 ± 3.8 mm. The location of the inferior alveolar canal on the mandibular ramus with respect to the anterior, posterior, lateral and medial borders were 11.1 ± 2.6 mm, 15.8 ± 2.7 mm, 3.5 ±1.0 mm y 1.9 ± 0.7 mm respectively. On the mandibular body, the distances from the inferior alveolar canal to the inferior, lateral, medial and alveolar borders were 10.1 ± 2.3 mm, 4.7 ± 1.4 mm, 2.5 ± 1.0 mm and 13.7±2.7 mm respectively distal to the third molar, 7.6 ± 1.7 mm, 6.4 ± 1.4 mm, 2.8 ± 1.0 mm and 16.4 ± 2.2 mm distal to the second molar, 7.1 ± 1.5 mm, 6.1 ± 1.3 mm, 2.6 ± 0.8 mm and 17.0 ± 2.3 mm distal to the first molar, and 7.9 ± 1.7 mm, 4.7 ± 1.2 mm, 3.4 ± 1.2 mm and 18.3 ± 2.7 mm distal to the second bicuspid. The diameter was 2.82 ± 0.6 mm. The distance from the mental foramen to the inferior border was 14.2 ± 1.59 mm, to the alveolar crest was 15.97 ± 2.87 mm, and it was directly related to the second bicuspid. Conclusions: The data obtained, even though, do not infer in the totality of the Colombian population, confirms that there are anatomical variations of the inferior alveolar canal different from the ones described for other populations.